2010
DOI: 10.1134/s1063773710070054
|View full text |Cite
|
Sign up to set email alerts
|

Brightness oscillations in models of young binary systems with low-mass secondary components

Abstract: We consider a model for the cyclic brightness variations of a young star with a low-mass companion that accretes matter from the remnants of a protostellar cloud. At small inclinations of the binary orbit to the line of sight, the streams of matter and the density waves excited in the circumbinary disk can screen the primary component of the binary from the observer. To study these phenomena, we have computed grids of hydrodynamic models for binary systems by the SPH method based on which we have constructed t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…The flow of matter in binary systems accreting material from protoplanetary disks has been simulated numerically in many studies [7][8][9][10][11][12][13][14][15][16][17]. The simulation results indicate the following major flow elements in these systems: circumstellar accretion disks around the system components, a rarefied area in the central parts of the protoplanetary disk adjoining the binary, and a complex system of gas-dynamical flows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow of matter in binary systems accreting material from protoplanetary disks has been simulated numerically in many studies [7][8][9][10][11][12][13][14][15][16][17]. The simulation results indicate the following major flow elements in these systems: circumstellar accretion disks around the system components, a rarefied area in the central parts of the protoplanetary disk adjoining the binary, and a complex system of gas-dynamical flows.…”
Section: Introductionmentioning
confidence: 99%
“…For reverse rotation to occur, the angular momentum delivered to the disk by the falling matter must be opposite to the angular momentum of the system. Numerical simulations of these systems have been performed in various studies [7][8][9][10][11][12][13][14][15][16][17], have not indicated the appearance of reversed accretion disks in binary systems for a wide range of parameters. In addition, analysis of the flow structure that forms in the vicinity of a young binary indicates that flows directed opposite to the motion of the components can exist [15].…”
Section: A Model For the Formation Of A Reversed Accretion Diskmentioning
confidence: 99%
“…This problem was initiated by the observations of large-scale activity cycles in UX Ori stars (Grinin et al 1998) and by the observations of anomalously long eclipses in some young stars (Cohen et al 2003; Barsunova et al 2005; Nordhagen et al 2006; Grinin et al 2008), which cannot be explained in terms of classical models of eclipsing binary systems. Sotnikova and and Demidova et al (2010aDemidova et al ( , 2010b showed that the streams of matter and density waves produced in young binary systems by the orbital motion of their companions can cause (at low inclinations of the orbital plane to the line of sight) various (in shape and duration) periodic fadings of the primary component. One of the main conditions in the computations was coplanarity of the orbital plane and the circumbinary (CB) disk.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous papers of this series (Sotnikova and Grinin 2007; Demidova et al 2010aDemidova et al , 2010b, we studied the behavior of the circumstellar extinction and brightness in young binary systems accreting matter from the remnants of a protostellar cloud. This problem was initiated by the observations of large-scale activity cycles in UX Ori stars (Grinin et al 1998) and by the observations of anomalously long eclipses in some young stars (Cohen et al 2003; Barsunova et al 2005; Nordhagen et al 2006; Grinin et al 2008), which cannot be explained in terms of classical models of eclipsing binary systems.…”
Section: Introductionmentioning
confidence: 99%
“…We used the input parameters to transform the column density of SPH particles to optical depth. Then, we calculated the theoretical brightness curves (see Demidova et al (2010) for more details).…”
Section: Overviewmentioning
confidence: 99%